2021
DOI: 10.1111/1755-0998.13550
|View full text |Cite
|
Sign up to set email alerts
|

Long‐read assembly of the Chinese indigenous Ningxiang pig genome and identification of genetic variations in fat metabolism among different breeds

Abstract: Advances in long-read sequencing technology and genome assembly provide an opportunity to improve the pig genome and reveal the full range of structural variations (SVs) between local Chinese and European pigs. To date, little is known about the genomes of some unique Chinese indigenous breeds, such as the Ningxiang pig. Here, we report the sequencing and assembly of a highly contiguous Ningxiang pig genome (NX) via an integration of PacBio single-molecule real-time sequencing, Illumina nextgeneration sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Despite the fundamental role of genome assemblies in biological studies, high‐quality assemblies are limited to well‐known domestic pig breeds. For example, all currently available chromosome‐level assemblies were from domestic breeds, including Duroc (Groenen et al, 2012; Warr et al, 2020), Bama (Zhang et al, 2019a), Luchuan (Yang et al, 2019), Ningxiang (Ma et al, 2022) and Meishan (Zhou et al, 2021), whereas the scaffold‐level assemblies also came from domestic breeds, including Wuzhishan (Fang et al, 2012), Large White, Landrace, Berkshire, Hampshire, Pietrain, Bamei, Jinhua, Rongchang and Tibetan (Li et al, 2017). For wild boars, there are some short‐read Illumina sequences (Bosse et al, 2015; Frantz et al, 2015; Groenen, 2016), but no assembly of a genome based on long‐reads or long‐range sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fundamental role of genome assemblies in biological studies, high‐quality assemblies are limited to well‐known domestic pig breeds. For example, all currently available chromosome‐level assemblies were from domestic breeds, including Duroc (Groenen et al, 2012; Warr et al, 2020), Bama (Zhang et al, 2019a), Luchuan (Yang et al, 2019), Ningxiang (Ma et al, 2022) and Meishan (Zhou et al, 2021), whereas the scaffold‐level assemblies also came from domestic breeds, including Wuzhishan (Fang et al, 2012), Large White, Landrace, Berkshire, Hampshire, Pietrain, Bamei, Jinhua, Rongchang and Tibetan (Li et al, 2017). For wild boars, there are some short‐read Illumina sequences (Bosse et al, 2015; Frantz et al, 2015; Groenen, 2016), but no assembly of a genome based on long‐reads or long‐range sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…When we combined the analysis of SV distribution and the location of gene gain and loss on the 3D4/21 cell chromosome, it was found that there was a close relationship between structural variation and gene function, which was consistent with previous reports. It has been found that the deletion of 281 bp in the first intron of MYL4 in Ningxiang pigs promoted the formation of subcutaneous fat [ 39 ], and the deletion of the intron of IGF2R in Tibetan pigs inhibited its growth rate [ 27 ]. By further combining Hi-C data, we found that the deletion of large fragments resulted in the change in 3D genomic domains in 3D4/21 cells, leading to gene dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the second-generation sequencing was the most commonly used method to analyze gene molecular mechanism in pig ( Liu et al, 2019b ; Tang et al, 2017 ). Recently, third-generation sequencing has been increasingly employed in studying the functional genomics and epigenetics in pig ( Beiki et al, 2019 ; Ma et al, 2021 ; Zhang et al, 2020 ). However, the AS and APA events in the pig ovary are rarely reported.…”
Section: Discussionmentioning
confidence: 99%